1966
DOI: 10.1104/pp.41.10.1615
|View full text |Cite
|
Sign up to set email alerts
|

Non-Existence of an Optimum Leaf Area Index for the Production Rate of White Clover Grown Under Constant Conditions

Abstract: Summary. Single clover plants were grown in the vegetative state, at 20 ± 10, 85 + 5 % relative humidity, 320 + 10 ppm CO, 12-hour day, with Hoagland nutrient in Perlite, and 100 w * m-2 of photosynthetically active radiation (0.4-0.7 ,u) from mercury-fluorescent lamps. Each plant was confined within a circle 18 cm in diameter by means of a wire framework. The COO exchange rate of the whole plant was measured every second day for 3 months. There was no optimum leaf area index for the net photosynthesis rate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

1970
1970
2006
2006

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…The course of respiration was similar in air and C02-free air, and for leaves from the field and growth room. 0 Others found that dark respiration of leaves (4,6) and whole plants (7,8) varied with prior illumination in air, but my experiments reveal that respiration is quantitatively related to prior illumination and not to net CO2 fixation. The stimulation of respiration in maize leaves differs in onset and duration from the postillumination burst of photorespiration (1,10), but resembles the enhancement by blue light of respiratory 02 uptake in starved cells of Chlorella (5,9).…”
Section: Resultsmentioning
confidence: 99%
“…The course of respiration was similar in air and C02-free air, and for leaves from the field and growth room. 0 Others found that dark respiration of leaves (4,6) and whole plants (7,8) varied with prior illumination in air, but my experiments reveal that respiration is quantitatively related to prior illumination and not to net CO2 fixation. The stimulation of respiration in maize leaves differs in onset and duration from the postillumination burst of photorespiration (1,10), but resembles the enhancement by blue light of respiratory 02 uptake in starved cells of Chlorella (5,9).…”
Section: Resultsmentioning
confidence: 99%
“…Sun and shade leaves differentiate within a stand and they have different photosynthetic capacities from each other (Boardman, 1977;Björkman, 1981). [McCree and Troughton (1966) suggested that the optimal LAI as assumed by Monsi and Saeki (1953) would not exist because shade leaves have a lower light compensation point.] However, Saeki (1959) noted that as the contribution of shaded leaves to total canopy photosynthesis was small, canopy photosynthesis calculated based on the photosynthesis of sun leaves gave virtually the same result as that calculated based on different photosynthetic capacities between sun and shade leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Past and current opinion favours leaf death as the major cause of reduced net growth rate at high Leaf Area Index (L.A.I.) values, so that at yield ceilings leaf production is offset by leaf death (Donald 1956;Barnard 1964;Bean 1964;Hunt 1965;Brougham 1966;McCree and Troughton 1966). Willoughby (1965) suggests that even in a seemingly highly utilised sward the amount of pasture lost through death and decay is generally underestimated.…”
Section: Introductionmentioning
confidence: 99%